Optimum Executive Body Has 5 Members Simple Mathematical Proof (Global Journal of Management and Business Research, 2015)
Intuitively we know that any executive body in any organization in order to be effective must have limited number of its members.. By means of simple mathematical procedures and ideas of the theory of information we prove that